Conversor CC-CC Trifásico Isolado Bidirecional com Entrada em Corrente, Comutação Suave e Comando Assimétrico Para Armazenamento de Energia - Costa, Gilmar Nunes dos Santos (2021)
This work presents the simulation study and analysis of a bidirectional isolated current-fed DCDC converter with soft switching. The proposed converter uses the phase-shift (PS) technique and variable cyclic ratio on the primary side, to perform power flow control. The phase-shift ensures the control of the magnitude and bidirectionality of the power flow, which is essential for connecting energy stores to voltage buses, such as batteries. The variable cyclic ratio allows for more flexible voltage adjustment on the low voltage capacitive bus. In the primary, there are three single-phase H bridges, and in the secondary, a traditional three-phase inverter. Both aspects are connected by a high frequency isolating transformer, which ensures galvanic isolation between the low and high voltage sides. The open-star delta configuration ensures double voltage, optimizing the functionality of the transformer and reducing copper losses. The mathematical modeling of the active and apparent power was carried out using two models: real and by analysis of the fundamental components. A comparison of the two models is carried out to validate the theoretical modeling performed in sets with the simulation results. The modeling and characterization of the switching of the switches are carried out, where, from this, the regions of soft switching of the type ZVS and dissipative switching are defined. . The simulation results showed a maximum error of 2.8% for active power and 3.4% for apparent power when compared with the theoretical results. The behavior of the switching of the switches through the boundary curves was also verified, which for the converter, through the adjustment of the cyclic ratio in the primary side, can establish optimal conditions of static gain and, consequently, allows the converter to operate in soft switching of the ZVS type for all switches.In closed loop, the results were satisfactory in terms of the performance of the converter, where a maximum overshot of 11.75 % was observed for sudden reversal of power flow (100% step to -100%)